Sibling rivalry management: An analytical study of prophet Yusuf's story - Angraini Ramli; Nurul Badriyah Ali; Azka Sa'dan (Atfaluna: Journal of Islamic Early Childhood Education, 2022)
This study aims to discuss the sibling rivalry behavior mentioned in the Quran involving Prophet Yusuf and his brothers, its causes, indications, effects and treatment as extracted from the story. This study uses a qualitative method with a descriptive-analytical approach involving various sources such as journals, books and classic literatures. The result of this study indicated that the causes of siblings encountered in the story of Prophet Yusuf as. were jealousy that builds an assumption of the existence of favoritism between siblings by parents, kids being competitive to get their parent's attention, lack of empathy for the sibling, harmful anger and manipulative attitude. To deal with this behavior, Prophet Yaqub showed an example as a distinctive parent by being patient with the children's behavior, playing fair with all his children, building good communication, and educating the children to always have a good connection with God.